Secondary Involvement of the Mandible due to Basal Cell Carcinoma: A Case Report - Mosannen Mozaffary, Pegah (Iran J Med Sci, 2015)
Basal cell carcinoma (BCC) is the most common cutaneous malignancy among Caucasians. Rare examples of aggressive and neglected BCC have been reported. Here we report a unique case of a neglected BCC with significant jaw involvement. A 50-year-old female, referred by an otorhinologist, presented with a large ulcer on her chin, which was extended to her mandibular vestibule. The ulcer was 9×5.5 cm in size, and tissue destruction, necrosis was observed in the central portion, and the mandibular bone was exposed. On intraoral examination, tooth mobility and severe bone loss were evident. Due to the primary cutaneous origin of the lesion, BCC was considered as preliminary diagnosis. Biopsy was performed and diagnosis of BCC was confirmed. The diseased mandibular bone was resected and reconstructed with a surgical plate. The soft tissue defect was reconstructed with deltopectoral flap. The patient refused secondary stage plastic surgery. Although BCC is not a lethal malignancy, if left untreated and neglected, it can result in severe destruction, disfigurement, and even mortality.